2011
DOI: 10.1186/1471-2105-12-214
|View full text |Cite
|
Sign up to set email alerts
|

Structator: fast index-based search for RNA sequence-structure patterns

Abstract: BackgroundThe secondary structure of RNA molecules is intimately related to their function and often more conserved than the sequence. Hence, the important task of searching databases for RNAs requires to match sequence-structure patterns. Unfortunately, current tools for this task have, in the best case, a running time that is only linear in the size of sequence databases. Furthermore, established index data structures for fast sequence matching, like suffix trees or arrays, cannot benefit from the complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…As in [23], we also support the description of an RNA molecule by multiple ordered sequence-structure patterns. In this way, the molecule’s secondary structure is decomposed into a sequence of substructures described by independent sequence-structure patterns.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…As in [23], we also support the description of an RNA molecule by multiple ordered sequence-structure patterns. In this way, the molecule’s secondary structure is decomposed into a sequence of substructures described by independent sequence-structure patterns.…”
Section: Introductionsupporting
confidence: 82%
“…This makes their application to large databases challenging. Previously, we addressed this problem by presenting Structator [23], an ultra fast index-based bidirectional matching tool that achieves sublinear running time by exploiting base pair complementarity constraints for search space reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research in molecular biology has revealed that ncRNAs are of fundamental importance in many biological processes, such as gene regulation, chromosome replication and RNA modification [3,12,25]. Recently, since the amount of fully sequenced data has grown explosively, computational search tools have become an important alternative for searching homologous RNA structures in genomic sequences and recognizing new ncRNAs [6,7,11,13]. In general, a genome is scanned through by a computational search tool during the search procedure and each sequence segment in the genome is aligned to a structural model that describes the secondary structure of the searched family.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, RNAmotif [13], RNAbob [6], Hypasearch [10,20] and Palingol [2] have been designed for the description of patterns as a succession of stems and loops, usually offering the possibility of choosing either a standard Watson-Crick pairing (A-U, G-C) or a pairing including Wobble (A-U, G-C, G-U). A more recent tool in this category, Structator [14], significantly improves the parsing time by making use of an index structure that is suited for the analysis of palindromic structures, the affix arrays. Patterns may also contain some sequence information on words that have to be present in particular places of the stems or the loops.…”
Section: Dedicated Pattern Matchingmentioning
confidence: 99%